2016
DOI: 10.1093/ajcp/aqw129
|View full text |Cite
|
Sign up to set email alerts
|

Detection ofCALRMutation in Clonal and Nonclonal Hematologic Diseases Using Fragment Analysis and Next-Generation Sequencing

Abstract: Screening for CALR mutations is essential in BCR-ABL-negative MPNs since it not only provides valuable diagnostic and prognostic information but also identifies potential treatment targets. Since this study describes the importance of screening for known and novel biomarkers, we described in detail three methods that could be easily integrated into a clinical laboratory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 27 publications
2
4
0
Order By: Relevance
“…Besides demonstrating JAK2 V617F acquired mutation, Klampfl et al [10] and Nangalia et al [11] demonstrated that the exon 9 of CALR coding sequence is exclusively mutated in approximately 70% of MPN patients who have negative results for JAK2 mutations. Interestingly, it was evident that CALR mutations are not present in PV, suggesting the utility of CALR mutations analysis for molecular classification of MPN [7,10,[25][26][27]. Similar to previous studies (Table 3) [17,25,28], we could detect 14% (8/58) of ET patients harboring CALR exon 9 frameshift mutations.…”
Section: Discussionsupporting
confidence: 86%
“…Besides demonstrating JAK2 V617F acquired mutation, Klampfl et al [10] and Nangalia et al [11] demonstrated that the exon 9 of CALR coding sequence is exclusively mutated in approximately 70% of MPN patients who have negative results for JAK2 mutations. Interestingly, it was evident that CALR mutations are not present in PV, suggesting the utility of CALR mutations analysis for molecular classification of MPN [7,10,[25][26][27]. Similar to previous studies (Table 3) [17,25,28], we could detect 14% (8/58) of ET patients harboring CALR exon 9 frameshift mutations.…”
Section: Discussionsupporting
confidence: 86%
“…Also, some researchers observed a lower frequency of JAK2 V617F mutation (31%) [18] and (35.7%) [19]. In the current series, the frequency of CALR (22%) is consistent with earlier reports [15,[20][21][22][23][24] but, higher than previous reports from Korea (17.7 %) [8], and Italy (14%) [25]. In concern to MPL W515L mutation, our observation (16.4%) is higher than earlier records that ranged from 1% to 14% [18,[25][26][27][28][29][30].…”
Section: Discussionsupporting
confidence: 91%
“…In their combined measurement, an OR of 3.5 was obtained (95% CI = 1.6–7.7). Eight studies used the WHO 2008 criteria [41, 4851, 54, 62, 66], for which an OR of 4.7 (95% CI = 3.1–7.5) was found. Three studies used WHO 2008 criteria and AS-PCR, and their combined measurement was an OR of 3.8 (95% CI = 1.6–8.3).…”
Section: Resultsmentioning
confidence: 99%